Re-imagining social-emotional learning: Findings from a strategy-based approach. (February 2019) - Bailey, Rebecca; Stickle, Laura; Brion-Meisels, Gretchen; Jones, Stephanie M.
Many schools and out-of-school organizations use social-emotional learning (SEL) programs to boost students' skills. Yet research shows that these programs can be difficult to implement and don't always meet students' needs. In response, Rebecca Bailey, Laura Stickle, Gretchen Brion-Meisels, and Stephanie Jones propose a new approach to SEL premised on three big ideas: SEL should be framed around a developmental model designed to target specific, age-appropriate skills; a flexible strategy-based approach may increase the feasibility of SEL implementation and school-wide consistency; and SEL is most effective when teachers are encouraged to implement and adapt strategies that meet their students' needs and reflect their experiences. The authors describe how such a program was implemented in a preK-8 summer program .